Characteristic of macroporous CeO2-ZrO2 oxygen carrier for chemical-looping steam methane reforming - 郑燕娥 祝星 王华 李孔斋 王禹皓 魏永刚 (Journal of rare earths, 2014)
Chemical-looping steam methane reforming （CL-SMR） is a novel process towards the production of pure hydrogen and syngas, consisting ofa syngas production reaction and a hydrogen production reaction. Macroporous CeQ-ZrO2 oxygen carders with different pore sizes prepared by colloidal crystal templating method and characterized by techniques of scalming electron microscopy （SEM）, transmission electron microscopy （TEM）, Brunauer-Emmett-Teller （BET）, X-ray diffraction （XRD） and temperature pro- grammed reduction （H2-TPR） were tested in CL-SMR process. For comparison, nonporous CeO2-ZrO2 oxygen carrier prepared by precipitation method was also investigated. It was found that macroporous CeO2-ZrO2 oxygen carriers owned higher reducibility and reactivity in CL-SMR process than nonporous samples. For the macroporous CeO2-ZrO2 sample, the decline of pore size could im- prove the reducibility and reactivity. The macroporous sample with a pore size of 100 nm （labeled as Ce-Zr-100） showed the highest performance for the co-production of syngas and hydrogen during the successive CL-SMR redox cycles. After 10 redox cycles, it still retained good porous structure and reducibility. It was found that the porous structure could accelerate the oxygen release from bulk to surface, leading to a good mobility of oxygen and higher reducibility. In addition, it was also favorable for diffusion and penetration of methane and water steam into the sample particles to accelerate the reaction rate.